Place of pharmaceutical industry in forming the quality of population life - Astratova, G.V.; Yakovlev, G.I.; Izmailov А.М. (BUKETOV BUSINESS REVIEW, 2017)
In the article presented by the authors, the question of the role of the pharmaceutical industry in shaping the quality of life of the population is examined. It is shown that the question of the quality of life of modern Russia occupies a priority place in the speeches of Russian politicians and economists. At the same time, the population may not always be in a state of prolonged emotional and social stress. It is extremely important to the orderly conduct of a deliberate government economic and social policy aimed at improving the level and quality of life of the population of Russia. In these circumstances, the development of medicine, the pharmaceutical industry can have a decisive importance for increasing the life expectancy of the population, the motivation to work, the implementation of a desire to create a family and raise children, and to form a Patriotic start. It is shown that it is necessary to form the national innovation system in the pharmaceutical industry, support advanced research and development to improve the level of their success.